Changes in the Viscoelastic Properties of the Vastus Lateralis Muscle With Fatigue - Chalchat, Emeric; Gennisson, Jean-Luc; Peñailillo, Luis; Oger, Myriam; Malgoyre, Alexandra; Charlot, Keyne; Bourrilhon, Cyprien; Siracusa, Julien; Garcia-Vicencio, Sebastian (Frontiers in Physiology, 2020)
We investigated the in vivo effects of voluntary fatiguing isometric contractions of the knee extensor muscles on the viscoelastic properties of the vastus lateralis (VL). Twelve young males (29.0 ± 4.5 years) performed an intermittent voluntary fatigue protocol consisting of repetitions 6 sets x 10 repetitions of 5-s voluntary maximal isometric contractions with 5-s passive recovery periods between repetitions. Voluntary and evoked torque were assessed before, immediately after, and 20 min after exercise. The shear modulus (µ) of the VL muscle was estimated at rest and during a ramped isometric contraction using a conventional elastography technique. An index of active muscle stiffness was then calculated (slope from the relationship between shear modulus and absolute torque). Resting muscle viscosity (ƞ) was quantified using a shear-wave spectroscopy sequence to measure the shear-wave dispersion. Voluntary and evoked torque decreased by ~37% (P < 0.01) immediately after exercise. The resting VL µ was lower at the end of the fatigue protocol (-57.9 ± 5.4%, P < 0.001), whereas the resting VL ƞ increased (179.0 ± 123%, P < 0.01). The active muscle stiffness index also decreased with fatigue (P < 0.05). By 20 min post-fatigue, there were no significant differences from the pre-exercise values for VL ƞ and the active muscle stiffness index, contrary to the resting VL µ. We show that the VL µ is greatly reduced and ƞ greatly enhanced by fatigue, reflecting a more compliant and viscous muscle. The quantification of both shear µ and ƞ moduli in vivo may contribute to a better understanding of the mechanical behavior of muscles during fatigue in sports medicine, as well as in clinical situations.